Children With Cerebral Palsy Can Run - Dedi Iskandar (Indonesian Journal of Education Teaching and Learning (IJETL), 2021)
The purpose of this study is to find out whether children with cerebral palsy can do physical motor activities, such as running. Another goal is to make the cerebral palsy child run. The method used is a data analysis method. Cerebral palsy children initially can not walk with the stimulus or therapy given the child can walk. The results obtained from the analysis of the data are cerebral palsy children can do physical motor activities such as running and other activities. Children with cerebral palsy are children with muscle disorders, tone, movements caused by disorders of the brain. Physical motor is an activity carried out in coordination between spiritual or physical movements and has an effect on the child's developmental stimulus.